Evaluation of fish assemblages’ composition in the Euphrates River, southern Thi-Qar province, Iraq - Abdullah, Abdul Hussein J. (Mesopotamian Journal of Marine Sciences, 2020)
Fish assemblage composition in the Euphrates River southern Thi-Qar province was assessed from January to December 2018. Various fishing methods were used to collect the samples. A total of 3010 specimens of bony fishes were caught represented 17 species, 17 genera, ten families and six orders. The species included ten native fish species and seven exotic fish species. The Abu mullet Planiliza abu was the most abundant species formed 26.21% of the total caught, blue tilapia Oreochromis aureus 19.30%, Prussian carp Carassius gibelio 17.48% and Redbelly tilapia Coptidon zillii 13. 29% of the total number of species. The dominance index (D3) value of the highest abundance represented by three fish species that preside the study area forming 62.99%, there are P. abu, O. aureus and C. gibelio. The occurrence of fish species contained seven fish species formed 92.03% of the total species caught. Seasonal fish species comprised of three fish species included 6.51% and occasional fish species contained seven species represented 1.46% of the total number of species. The diversity index values appear as poor ranged from 1.59 in December to 2.07 in April. Richness index values pointed to disturbing status, varied from 1.21 in September to 2.00 in May. Evenness index tends to be balanced, fluctuated from 0.79 in June to 0.91 in February and July. The present study verified the prevalence of the small-sized tolerance fish species represented by one native and three exotic species, with rarely or absence of the keystone native fish species of fish communities predominating the south of Iraq.